Climax as Work: Heteronormativity, Gender Labor, and the Gender Gap in Orgasms. Issue 2 (April 2022) - Andrejek, Nicole; Fetner, Tina; Heath, Melanie
Gender scholars have addressed a variety of gender gaps between men and women, including a gender gap in orgasms. In this mixed-methods study of heterosexual Canadians, we examine how men and women engage in gender labor that limits women's orgasms relative to men. With representative survey data, we test existing hypotheses that sexual behaviors and relationship contexts contribute to the gender gap in orgasms. We confirm previous research that sexual practices focusing on clitoral stimulation are associated with women's orgasms. With in-depth interview data from a subsample of 40 survey participants, we extend this research to show that both men and women engage in gender labor to explain and justify the gender gap in orgasms. Relying on an essentialist view of gender, a narrow understanding of what counts as sex, and moralistic language that recalls the sexual double standard, our participants craft a narrative of women's orgasms as work and men's orgasms as natural. The work to produce this gendered narrative of sexuality mirrors the gender labor that takes place in the bedroom, where both women and men engage in sexual behaviors that emphasize men's pleasure to a greater extent than women's.